Lilium saccatum: A new synonym of L. souliei (Liliaceae) for Flora of China - Yang, Lang-Sheng; Zhuang, Guo-Qing (Phytotaxa, 2015)
Lilium saccatum S. Y. Liang (1987: 540) was published in the Flora of Xizangica based on the material of Qinghai-Xizang Expedition (No. 74-3754) collected on July 30th, 1974. In the protologue, the author compared this species to L. souliei (Franchet) Sealy (1950: 296) and indicated that the former had basally saccate tepals compared to the latter, and based on this point the new species was recognized. However, the original description and type specimens of L. souliei has already displayed this feature (Fig. 3J–M in Sealy 1950; our Fig. 1A), until now, this feature has not been listed in both the Flora of Reipublicae Popularis Sinicae (Liang 1980), and Flora of China (Liang & Tamura 2000).